The role of product architecture in the manufacturing firm - Ulrich, Karl (Research Policy, 1995)
Product architecture is the scheme by which the function of a product is allocated to physical components. This paper further defines product architecture, provides a typology of product architectures, and articulates the potential linkages between the architecture of the product and five areas of managerial importance: (1) product change; (2) product variety; (3) component standardization; (4) product performance; and (5) product development management. The paper is conceptual and foundational, synthesizing fragments from several different disciplines, including software engineering, design theory, operations management and product development management. The paper is intended to raise awareness of the far-reaching implications of the architecture of the product, to create a vocabulary for discussing and addressing the decisions and issues that are linked to product architecture, and to identify and discuss specific trade-offs associated with the choice of a product architecture.